Gender inequalities: national evidence by activity sectors in the portuguese labour market - Nunes, Alcina (2020)
The gender occupational segregation is a negative phenomenon which still remains a common feature to the most diverse cultures and economies in the 21st century. One of the ways in which it is embodied is in wages and salary differences. Thus, this paper aims to identify and analyse the influence of the economic activities and the regional distribution of those same activities on the evolution of the average dissimilarity remuneration of Portuguese workers between 2010 and 2013. The variable under survey is the difference between the average monthly income, and the analysis was made by using the shift-share methodology. The productive structure and regional competitiveness have proven to be decisive in the wage gap.